2011
DOI: 10.4103/0972-124x.85667
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and periodontitis: A clinical study

Abstract: Background:The aim of the study was to evaluate the relationship between obesity and periodontitis.Materials and Methods:A total of 300 subjects aged 20 years and above suffering from generalized periodontitis were recruited from Department of Periodontics, Pacific Dental College and Hospital, Udaipur. Periodontal status of the subjects was recorded. Body mass index and waist circumference were used as measure to assess obesity. Other variables like age, gender, oral hygiene index were also recorded.Results:Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
3
17
1
8
Order By: Relevance
“…In the study group the frequency of periodontal disorders was high, similar to that reported by Mathur et al 7 , Cornejo et al 13 and Petelin et al 14 , but much higher than that reported by Norderyd et al 12 , Konopka et al…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the study group the frequency of periodontal disorders was high, similar to that reported by Mathur et al 7 , Cornejo et al 13 and Petelin et al 14 , but much higher than that reported by Norderyd et al 12 , Konopka et al…”
Section: Discussionsupporting
confidence: 69%
“…It can increase the risk for the emergence of other systemic diseases (cardiovascular, metabolic and neurological) and local, such as PD [7][8][9][10] . It is a nutritional disorder and is considered a public health problem because its prevalence has doubled in the last two decades worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is considered a chronic, complex and multifactorial condition, and it is related to lifestyle, hyper-caloric diet, sedentary lifestyle, as well as endocrine and/or metabolic disorders, resulting in the increase of hip and abdominal circumference and alterations of body weight 3 . Fat tissue is metabolically active, and it is able to produce pro-inflammatory cytokines or adipokines, such as the inhibitor of plasminogen activator, which increase the risk for vascular diseases due to the decrease in blood flow, which could explain one of the mechanisms involved in the exacerbation of the severity and progression of periodontal diseases 4 .…”
Section: Introductionmentioning
confidence: 99%
“…O acúmulo de placa bacteriana nas superfícies dentárias está associado com a presença de alterações bucais como a presença de sangramento gengival e de cálculo dentário, e consequentemente à doença periodontal (IRIGOYEN-CAMACHO et al, 2014;FRANCHINI et al, 2011). Os obesos avaliados neste estudo (G1 e G2) apresentaram pobres condições de higiene bucal na avaliação inicial (Tabela 4), dado que vai ao encontro do exposto na literatura científica (KIM et al, 2014;AKMAN et al, 2012;DE CASTILHOS et al, 2012;MATHUR et al, 2011;ZERMENO-IBARRA et al, 2010).…”
Section: Condições Periodontais E De Higiene Bucalunclassified
“…Um estudo conduzido com indivíduos adultos na Índia relatou as más condições de higiene bucal e a associações entre a DP e a obesidade (MATHUR et al, 2011). A gordura corporal pode desempenhar um importante papel no desenvolvimento de doenças crônicas, como a periodontite, teoria suportada pelo estudo de Gorman e colaboradores (2012) que acompanharam uma coorte de homens e observaram que os indivíduos que ganharam peso de forma mais rápida apresentaram progressão mais acentuada da DP (GORMAN et al, 2012).…”
unclassified